The Effect of Cinnamon Supplementation on Hemoglobin A1c in Patients with Type 1 Diabetes Mellitus - Salehpour, Shadab; Saneifard, Hedyeh; Alaei, Mohammadreza; Shakiba, Marjan; Ghanefard, Shirin (Archives of Men’s Health, 2023)
Introduction: Type 1 diabetes mellitus (T1DM), one of the most common endocrine disorders in children, is an autoimmune disease that manifests itself as an increase in blood sugar as a result of impaired insulin production due to the destruction of the islets of Langerhans in the pancreas. To treat this disease, along with the use of insulin and numerous drug protocols, the use of herbal medicinal supplements has always been considered. However, due to the lack of studies related to these supplements, there is not enough evidence for their therapeutic use. Method: We investigated the therapeutic effectiveness of a cinnamon medicinal supplement with a dose of 50 mg every 8 hours per day, on glucose hemostasis in patients with T1DM . Thirty patients with T1DM were enrolled. They are subjected to sampling and examination of blood sugar indicators, including fasting blood sugar and hemoglobin A1c, as well as indicators of insulin consumption (total daily dose of insulin) and insulin resistance, including the ratio of insulin to carbohydrates on days 0, 90 and 180 of the start of treatment with cinnamon. Results: The level of hemoglobin A1c in this group had a significant decrease. Also, there was no significant increase in the amount of insulin consumption in the drug supplement-consuming groups in contrast to the control group during six months. Conclusion: The use of cinnamon supplements along with treatment protocols has a significant effect in reducing hemoglobin A1c during six months of treatment in these patients. These results can be useful in promoting the use of therapeutic supplements in the treatment of patients with diabetes.